2014
DOI: 10.1111/cas.12503
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitogen‐activated protein kinase pathway can induce upregulation of human leukocyte antigen class I without PD‐L1‐upregulation in contrast to interferon‐γ treatment

Abstract: Recently, we reported that human leukocyte antigen (HLA) class I expression is predominantly regulated by the mitogen-activated protein kinase (MAPK) pathway as one of the oncogenic regulations of HLA class I expression. In the present study, we examined mechanisms of how HLA class I and PD-L1 are regulated by MAPK inhibitors and interferon-γ (IFN-γ). Furthermore, we evaluated the expression of major signal transduction molecules by Western blot and anti-tumor CTL activity by a cytotoxic assay when HLA class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 33 publications
6
45
0
Order By: Relevance
“…To evaluate the effect of the PD‐1/PD‐L1 interaction on anti‐tumor CTL activity, HLA‐A24‐positive, LY6K‐positive tumor cells, namely MKN7 and TE1, were pre‐treated with or without IFN‐γ for 48 hour. The cells were then treated with anti‐PD‐L1 mAb or isotype control for 1 hour and subjected to cytotoxic assay.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…To evaluate the effect of the PD‐1/PD‐L1 interaction on anti‐tumor CTL activity, HLA‐A24‐positive, LY6K‐positive tumor cells, namely MKN7 and TE1, were pre‐treated with or without IFN‐γ for 48 hour. The cells were then treated with anti‐PD‐L1 mAb or isotype control for 1 hour and subjected to cytotoxic assay.…”
Section: Resultssupporting
confidence: 92%
“…An isotype‐matched immunoglobulin served as a negative control, and staining was detected using an LSRII flow cytometer (Becton Dickinson). Dead and/or apoptotic cells were excluded using Annexin‐V and 7‐Aminoactinomycin D. The relative mean fluorescence intensity (rMFI) was calculated according to the formula: [(MFI with specific mAb − MFI with isotype mAb)/MFI with isotype mAb]/[(MFI with specific mAb of control treatment − MFI with isotype mAb of control treatment)/MFI with isotype mAb of control treatment] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 IFN-g sensitizes target cells to killing by diverse mechanisms, including modulation of HLA expression, 62,63 production of nitric oxide, 3 activation of caspase death pathways, [64][65][66] and induction of Fas expression. [44][45][46]67 We previously reported that Fas/FasL is the major cell death pathway for marrow destruction For personal use only.…”
Section: Cd48mentioning
confidence: 99%